Supplementation of Banana By-products Hay does not Alter Serum Biochemistry of Lambs - L. K. G. Barbosa; N. C. Silva; N. J. F. Oliveira; R. A. C. Passetti; L. C. Geraseev (Tropical Animal Science Journal, 2023)
In this study, we evaluated the serum profile of sheep fed with banana residue hays dried using two methods. Thirty crossbred Santa Inês × Dorper, male, non-castrated sheep (average body weight = 26.5 kg) were distributed in a randomized block design with five treatments: control, two types of residues (banana pseudo stem and banana leaf hays), and two drying methods (sun and shade drying). After feeding the experimental diets for 20 days, the animals were fasted for 12 h before collecting venous blood (6 mL) for plasma and serum at 0, 3, and 6 h after feeding. Variance analysis was performed in subdivided plots, and the means were compared using Dunnett’s test at 5% probability. No differences were observed in the dry matter intake of animals fed with banana by-product hay; however, the in vitro dry matter digestibility was high for pseudo stem hay. The differences in the nutritional value of the hays were not sufficient to alter the serum biochemistry of the animals. No differences were observed in the total protein, serum albumin and globulins, albumin/globulin ratio, and plasma glucose among time points and treatments (5.83 g/dL, 3.43 g/dL, 2.40 g/dL, 1.82 g/dL, and 64.6 mg/dL). Urea and triglyceride levels were the highest (p<0.05) at 3 h after feeding (30.1 and 37.0 mg/dL, respectively) and creatinine at 0 h (0.94 mg/dL). Serum cholesterol levels were the lowest (p<0.05) at 3 h after feeding (38.5 mg/dL). No effect of treatment on these parameters was observed. Thus, sheep can be fed with pseudo stem or banana leaves dehydrated in the sun or shade without compromising blood parameters.